2020
DOI: 10.3390/agronomy10030434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice Residue Retention and Foliar Application of K on Water Productivity and Profitability of Wheat in North West India

Abstract: The rice–wheat cropping system being the backbone of food security in South-Asia has resulted in soil health deterioration, declining water table, and air pollution affecting livability index of the region. The effect of rice residue retention (RRR), irrigation levels and foliar application of K on wheat grain yield (GY), water use efficiency (WUE) and profitability was tested over three years. RRR increased wheat GY (5224 kg ha−1), above-ground biomass (AGBM = 11.9 t ha−1), tillers per square meter (TPM = 469… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In addition, transplanted rice had maximum RWC of 87.3%. Residue mulching on soil surface decreases the evaporative water losses, maintains soil moisture for longer time, reduces the weed growth and moderates the soil temperature (Meena et al 2020). All these beneficial effects might lead to improved water uptake by crop plants which maintained higher RWC in leaves.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, transplanted rice had maximum RWC of 87.3%. Residue mulching on soil surface decreases the evaporative water losses, maintains soil moisture for longer time, reduces the weed growth and moderates the soil temperature (Meena et al 2020). All these beneficial effects might lead to improved water uptake by crop plants which maintained higher RWC in leaves.…”
Section: Resultsmentioning
confidence: 99%
“…In an investigation, Ramos et al and Khan et al [8,9] concluded that traditional soil management practices effect the nutrients volume in soil and availability to plant for better production. RWCS in IGP produces around 10 to 12 Mg-ha residues [10,11] which were taken off or burned before sowing of the next crop. Burning or the removal of residues are adversely affecting the soil physio-chemical properties, especially nutrients such as macro and micronutrients [12].…”
Section: Introductionmentioning
confidence: 99%
“…The K is one of the critical nutrient essentials for wheat plants, possessing primary roles in the processes of cell extension and osmoregulation, stomatal movement, protein synthesis, activation of enzymes, phloem loading, photosynthesis, transport, and uptake (Marschner, 1995;Pettigrew, 2008). Meena et al (2020) reported that the WUE of wheat increased significantly with foliar application of K. Alike, Wang et al (2020) documented that a higher net photosynthesis rate appears when applied with a high dose of K.…”
Section: Discussionmentioning
confidence: 99%